2008
DOI: 10.1002/tea.20255
|View full text |Cite
|
Sign up to set email alerts
|

Teaching science as a language: A “content‐first” approach to science teaching

Abstract: Our research project was guided by the assumption that students who learn to understand phenomena in everyday terms prior to being taught scientific language will develop improved understanding of new concepts. We used web-based software to teach students using a ''content-first'' approach that allowed students to transition from everyday understanding of phenomena to the use of scientific language. This study involved 49 minority students who were randomly assigned into two groups for analysis: a treatment gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(128 citation statements)
references
References 34 publications
5
113
0
6
Order By: Relevance
“…We take this to be a very important finding for science educators. These findings give further support to the conclusions of Brown and Ryoo (2008) to encourage teachers to make use of students' non-scientific expressions and that everyday language is a valuable resource in the students' struggle to come to terms with scientific concepts and terminology.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We take this to be a very important finding for science educators. These findings give further support to the conclusions of Brown and Ryoo (2008) to encourage teachers to make use of students' non-scientific expressions and that everyday language is a valuable resource in the students' struggle to come to terms with scientific concepts and terminology.…”
Section: Discussionsupporting
confidence: 71%
“…When a learner meets new, unknown, scientific concepts the only way to make sense of them is to relate them to previously known concepts, previous experience, and to formulate an understanding by using the scientific or non-scientific language and other communicative resources that he or she already possesses. A study by Brown and Ryoo (2008) showed that better learning outcomes occurred when the instruction was first given using everyday language to explain the scientific content and then scientific language was introduced, rather than the other way around.…”
mentioning
confidence: 99%
“…Bruner (1966Bruner ( , 1986, Lemke (1990), Taber (2000), Driver et al (2000), Newton (2002), Mercer et al (2004) and, more recently, Brown and his coauthors (Brown and Ryoo 2008;Brown et al 2010;Brown and Spang 2008), for example, concentrate on how thinking may be scaffolded (to use Bruner's term for the sociocultural learning process exemplified by Vygotsky's zone of proximal development (ZPD); see Foley 1994;Mooney 2000). From an ethnographic perspective, Brown and colleagues' work has emphasised the linguistic dimensions of scaffolding.…”
Section: Scaffoldingmentioning
confidence: 99%
“…Därmed kan denna typ av analyser också användas som ett didaktiskt verktyg av lärare och lärarstudenter för att explicitgöra språkliga perspektiv på elevers lärande i naturvetenskaplig undervisning, vilket exempelvis kan leda till att gruppsamtal planeras och utformas utifrån föresatsen att de ska gynna elevernas utveckling av naturvetenskapliga resonemang och uttryckssätt. En sådan slutsats får också stöd i senare års forskning inom naturvetenskapernas didaktik som visar att en medveten användning av och växling mellan vardagliga och vetenskapliga språkbruk gynnar elevers lärande i de naturvetenskapliga äm-nena (Ash, 2008;Brown & Spang, 2008;Brown & Ryoo, 2008). I analysen är det möjligt att upptäcka ett flertal exempel där enskilda elever i en och samma konversation använder både ett vardagligt och ett mer ämnesspecifikt språkbruk.…”
Section: Diskussionunclassified